2010
DOI: 10.1007/s12223-010-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Campylobacter jejuni to organic acids and monoacylglycerols

Abstract: Organic acids can be used as feed supplements or for treatment of poultry carcasses in processing plants. The antimicrobial activity of nineteen organic acids and two monoacylglycerols in cultures of Campylobacter jejuni CCM 6214(T) (ATCC 33560) was determined using a SYBR Green-based real-time PCR assay. The IC(50) was a concentration at which only 50 % of a bacteria specific DNA sequence was amplified. Caprylic, capric and lauric acids were the most efficient antimicrobials among the compounds tested (IC(50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…Salmonella species were susceptible to caproic acid (Van Immerseel et al 2004) and caprylic acid (Skřivanová et al 2004). Thormar et al (2006) found that capric acid and monocaprin were more efficient against Campylobacter jejuni as compared with caprylic acid and monocaprylin, this observation having been confirmed by Molatová et al (2010). Depending on the monocaprylin concentrations and the temperatures examined, increasing temperature enhanced the bactericidal activity of monocaprylin, which can be partially explained by an increase in solubility.…”
Section: Dbm 3157mentioning
confidence: 87%
See 2 more Smart Citations
“…Salmonella species were susceptible to caproic acid (Van Immerseel et al 2004) and caprylic acid (Skřivanová et al 2004). Thormar et al (2006) found that capric acid and monocaprin were more efficient against Campylobacter jejuni as compared with caprylic acid and monocaprylin, this observation having been confirmed by Molatová et al (2010). Depending on the monocaprylin concentrations and the temperatures examined, increasing temperature enhanced the bactericidal activity of monocaprylin, which can be partially explained by an increase in solubility.…”
Section: Dbm 3157mentioning
confidence: 87%
“…Reports on the effects of capric acid, lauric acid, and monocaprin on Cronobacter, which is a Gram-negative bacterium and thus less susceptible to antimicrobials relative to Gram-positive bacteria, are absent from the current literature. In contrast, reports exist on the antimicrobial action of MCFAs and monoacylglycerols against several other Gram-negative food-borne pathogens that include e. coli (Hassinen et al 1951;Petschow et al 1998;Marounek et al 2003), Salmonella (Skřivanová et al 2004;Van Immerseel et al 2004) and Campylobacter jejuni (Thormar et al Molatová et al 2010). The antimicrobial actions of MCFAs and monoacylglycerols in these studies were variable, and strain-to-strain variability of the susceptibility of different bacteria to these antimicrobials was apparent.…”
Section: Dbm 3157mentioning
confidence: 94%
See 1 more Smart Citation
“…The suspension was incubated for another 3 min or until the values did not rise anymore. Values were automatically recorded every 3 s. The detailed description of this technique has already been used and published (Ohmizo et al 2004;Molatova et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Molatová et al (2010) demonstrated that fumaric acid had clear antimicrobial activity to Campylobacter jejun. Kim et al (2001) reported that fumaric acid isolated from Camellia japonica L. produced an inhibitory activity against the pathogens Salmonella typhimurium, E. coli, Listeria monocytogenes and S. aureus.…”
Section: Chemical Groupmentioning
confidence: 99%